2005
DOI: 10.1016/j.bbamem.2005.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of triorganotin compounds on membrane permeability

Abstract: Organotin compounds are widely distributed toxicants. They are membrane-active molecules with broad biological toxicity. In this contribution, we study the effect of triorganotin compounds on membrane permeability using phospholipid model membranes and human erythrocytes. Tribultyltin and triphenyltin are able to induce the release of entrapped carboxyfluorescein from large unilamellar vesicles. The rate of release is similar for phosphatidylcholine and phosphatidylserine systems and the presence of equimolar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 37 publications
1
24
0
1
Order By: Relevance
“…It has been reported that inclusion of up to 50% cholesterol in phosphatidylcholine membranes almost completely inhibited the passive membrane permeation to CF and ions [36], contents leakage induced by environmental toxicants [37], and surfactant-induced leakage [38]. In lipid bilayers, cholesterol affects the lipid chain order of phospholipids and thus modulates the membrane mechanical properties [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that inclusion of up to 50% cholesterol in phosphatidylcholine membranes almost completely inhibited the passive membrane permeation to CF and ions [36], contents leakage induced by environmental toxicants [37], and surfactant-induced leakage [38]. In lipid bilayers, cholesterol affects the lipid chain order of phospholipids and thus modulates the membrane mechanical properties [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Phenyltins are chemicals with welldocumented biological activity and with the capability to cross the lipid bilayer by passive diffusion [1,11,12]. It has been shown previously that adsorption of such compounds results in the electrostatic surface potential generation which can be detected with the fluorescent probe located at both membrane surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…The decrease in cultured heart cell viability could be explained by the induction of apoptosis and/or necrosis. The lipophilic nature of TBT makes it an active membrane toxicant (Ortiz et al 2005). It was demonstrated using flow cytometry and YO-PRO r staining that around 10% of cells are apoptotic and necrotic after only 10 min of treatment with 10 −6 M TBT.…”
Section: Discussionmentioning
confidence: 99%